module plfa.part2.Substitution where


## Introduction

The primary purpose of this chapter is to prove that substitution commutes with itself. Barendgredt (1984) refers to this as the substitution lemma:

M [x:=N] [y:=L] = M [y:=L] [x:= N[y:=L] ]


In our setting, with de Bruijn indices for variables, the statement of the lemma becomes:

M [ N ] [ L ] ≡  M〔 L 〕[ N [ L ] ]                     (substitution)


where the notation M 〔 L 〕 is for substituting L for index 1 inside M. In addition, because we define substitution in terms of parallel substitution, we have the following generalization, replacing the substitution of L with an arbitrary parallel substitution σ.

subst σ (M [ N ]) ≡ (subst (exts σ) M) [ subst σ N ]    (subst-commute)


The special case for renamings is also useful.

rename ρ (M [ N ]) ≡ (rename (ext ρ) M) [ rename ρ N ]
(rename-subst-commute)


The secondary purpose of this chapter is to define the σ algebra of parallel substitution due to Abadi, Cardelli, Curien, and Levy (1991). The equations of this algebra not only help us prove the substitution lemma, but they are generally useful. Furthermore, when the equations are applied from left to right, they form a rewrite system that decides whether any two substitutions are equal.

## Imports

import Relation.Binary.PropositionalEquality as Eq
open Eq using (_≡_; refl; sym; cong; cong₂; cong-app)
open Eq.≡-Reasoning using (begin_; _≡⟨⟩_; _≡⟨_⟩_; _∎)
open import Function using (_∘_)
open import plfa.part2.Untyped
using (Type; Context; _⊢_; ★; _∋_; ∅; _,_; Z; S_; _; ƛ_; _·_;
rename; subst; ext; exts; _[_]; subst-zero)

postulate
extensionality : ∀ {A B : Set} {f g : A → B}
→ (∀ (x : A) → f x ≡ g x)
-----------------------
→ f ≡ g


## Notation

We introduce the following shorthand for the type of a renaming from variables in context Γ to variables in context Δ.

Rename : Context → Context → Set
Rename Γ Δ = ∀{A} → Γ ∋ A → Δ ∋ A


Similarly, we introduce the following shorthand for the type of a substitution from variables in context Γ to terms in context Δ.

Subst : Context → Context → Set
Subst Γ Δ = ∀{A} → Γ ∋ A → Δ ⊢ A


We use the following more succinct notation the subst function.

⟪_⟫ : ∀{Γ Δ A} → Subst Γ Δ → Γ ⊢ A → Δ ⊢ A
⟪ σ ⟫ = λ M → subst σ M


## The σ algebra of substitution

Substitutions map de Bruijn indices (natural numbers) to terms, so we can view a substitution simply as a sequence of terms, or more precisely, as an infinite sequence of terms. The σ algebra consists of four operations for building such sequences: identity ids, shift ↑, cons M • σ, and sequencing σ ⨟ τ. The sequence 0, 1, 2, ... is constructed by the identity substitution.

ids : ∀{Γ} → Subst Γ Γ
ids x =  x


The shift operation ↑ constructs the sequence

1, 2, 3, ...


and is defined as follows.

↑ : ∀{Γ A} → Subst Γ (Γ , A)
↑ x =  (S x)


Given a term M and substitution σ, the operation M • σ constructs the sequence

M , σ 0, σ 1, σ 2, ...


This operation is analogous to the cons operation of Lisp.

infixr 6 _•_

_•_ : ∀{Γ Δ A} → (Δ ⊢ A) → Subst Γ Δ → Subst (Γ , A) Δ
(M • σ) Z = M
(M • σ) (S x) = σ x


Given two substitutions σ and τ, the sequencing operation σ ⨟ τ produces the sequence

⟪τ⟫(σ 0), ⟪τ⟫(σ 1), ⟪τ⟫(σ 2), ...


That is, it composes the two substitutions by first applying σ and then applying τ.

infixr 5 _⨟_

_⨟_ : ∀{Γ Δ Σ} → Subst Γ Δ → Subst Δ Σ → Subst Γ Σ
σ ⨟ τ = ⟪ τ ⟫ ∘ σ


For the sequencing operation, Abadi et al. use the notation of function composition, writing σ ∘ τ, but still with σ applied before τ, which is the opposite of standard mathematical practice. We instead write σ ⨟ τ, because semicolon is the standard notation for forward function composition.

## The σ algebra equations

The σ algebra includes the following equations.

(sub-head)  ⟪ M • σ ⟫ ( Z) ≡ M
(sub-tail)  ↑ ⨟ (M • σ)    ≡ σ
(sub-η)     (⟪ σ ⟫ ( Z)) • (↑ ⨟ σ) ≡ σ
(Z-shift)   ( Z) • ↑      ≡ ids

(sub-id)    ⟪ ids ⟫ M      ≡ M
(sub-app)   ⟪ σ ⟫ (L · M)  ≡ (⟪ σ ⟫ L) · (⟪ σ ⟫ M)
(sub-abs)   ⟪ σ ⟫ (ƛ N)    ≡ ƛ ⟪ σ ⟫ N
(sub-sub)   ⟪ τ ⟫ ⟪ σ ⟫ M  ≡ ⟪ σ ⨟ τ ⟫ M

(sub-idL)   ids ⨟ σ        ≡ σ
(sub-idR)   σ ⨟ ids        ≡ σ
(sub-assoc) (σ ⨟ τ) ⨟ θ    ≡ σ ⨟ (τ ⨟ θ)
(sub-dist)  (M • σ) ⨟ τ    ≡ (⟪ τ ⟫ M) • (σ ⨟ τ)


The first group of equations describe how the • operator acts like cons. The equation sub-head says that the variable zero Z returns the head of the sequence (it acts like the car of Lisp). Similarly, sub-tail says that sequencing with shift ↑ returns the tail of the sequence (it acts like cdr of Lisp). The sub-η equation is the η-expansion rule for sequences, saying that taking the head and tail of a sequence, and then cons’ing them together yields the original sequence. The Z-shift equation says that cons’ing zero onto the shifted sequence produces the identity sequence.

The next four equations involve applying substitutions to terms. The equation sub-id says that the identity substitution returns the term unchanged. The equations sub-app and sub-abs says that substitution is a congruence for the lambda calculus. The sub-sub equation says that the sequence operator ⨟ behaves as intended.

The last four equations concern the sequencing of substitutions. The first two equations, sub-idL and sub-idR, say that ids is the left and right unit of the sequencing operator. The sub-assoc equation says that sequencing is associative. Finally, sub-dist says that post-sequencing distributes through cons.

## Relating the σ algebra and substitution functions

The definitions of substitution N [ M ] and parallel substitution subst σ N depend on several auxiliary functions: rename, exts, ext, and subst-zero. We shall relate those functions to terms in the σ algebra.

To begin with, renaming can be expressed in terms of substitution. We have

rename ρ M ≡ ⟪ ren ρ ⟫ M               (rename-subst-ren)


where ren turns a renaming ρ into a substitution by post-composing ρ with the identity substitution.

ren : ∀{Γ Δ} → Rename Γ Δ → Subst Γ Δ
ren ρ = ids ∘ ρ


When the renaming is the increment function, then it is equivalent to shift.

ren S_ ≡ ↑                             (ren-shift)

rename S_ M ≡ ⟪ ↑ ⟫ M                  (rename-shift)


Renaming with the identity renaming leaves the term unchanged.

rename (λ {A} x → x) M ≡ M             (rename-id)


Next we relate the exts function to the σ algebra. Recall that the exts function extends a substitution as follows:

exts σ =  Z, rename S_ (σ 0), rename S_ (σ 1), rename S_ (σ 2), ...


So exts is equivalent to cons’ing Z onto the sequence formed by applying σ and then shifting.

exts σ ≡  Z • (σ ⨟ ↑)                (exts-cons-shift)


The ext function does the same job as exts but for renamings instead of substitutions. So composing ext with ren is the same as composing ren with exts.

ren (ext ρ) ≡ exts (ren ρ)            (ren-ext)


Thus, we can recast the exts-cons-shift equation in terms of renamings.

ren (ext ρ) ≡  Z • (ren ρ ⨟ ↑)       (ext-cons-Z-shift)


It is also useful to specialize the sub-sub equation of the σ algebra to the situation where the first substitution is a renaming.

⟪ σ ⟫ (rename ρ M) ≡ ⟪ σ ∘ ρ ⟫ M       (rename-subst)


The subst-zero M substitution is equivalent to cons’ing M onto the identity substitution.

subst-zero M ≡ M • ids                (subst-Z-cons-ids)


Finally, sequencing exts σ with subst-zero M is equivalent to cons’ing M onto σ.

exts σ ⨟ subst-zero M ≡ (M • σ)       (subst-zero-exts-cons)


## Proofs of sub-head, sub-tail, sub-η, Z-shift, sub-idL, sub-dist, and sub-app

We start with the proofs that are immediate from the definitions of the operators.

sub-head : ∀ {Γ Δ} {A} {M : Δ ⊢ A}{σ : Subst Γ Δ}
→ ⟪ M • σ ⟫ ( Z) ≡ M

sub-tail : ∀{Γ Δ} {A B} {M : Δ ⊢ A} {σ : Subst Γ Δ}
→ (↑ ⨟ M • σ) {A = B} ≡ σ
sub-tail = extensionality λ x → refl

sub-η : ∀{Γ Δ} {A B} {σ : Subst (Γ , A) Δ}
→ (⟪ σ ⟫ ( Z) • (↑ ⨟ σ)) {A = B} ≡ σ
sub-η {Γ}{Δ}{A}{B}{σ} = extensionality λ x → lemma
where
lemma : ∀ {x} → ((⟪ σ ⟫ ( Z)) • (↑ ⨟ σ)) x ≡ σ x
lemma {x = Z} = refl
lemma {x = S x} = refl

Z-shift : ∀{Γ}{A B}
→ (( Z) • ↑) ≡ ids {Γ , A} {B}
Z-shift {Γ}{A}{B} = extensionality lemma
where
lemma : (x : Γ , A ∋ B) → (( Z) • ↑) x ≡ ids x
lemma Z = refl
lemma (S y) = refl

sub-idL : ∀{Γ Δ} {σ : Subst Γ Δ} {A}
→ ids ⨟ σ ≡ σ {A}
sub-idL = extensionality λ x → refl

sub-dist :  ∀{Γ Δ Σ : Context} {A B} {σ : Subst Γ Δ} {τ : Subst Δ Σ}
{M : Δ ⊢ A}
→ ((M • σ) ⨟ τ) ≡ ((subst τ M) • (σ ⨟ τ)) {B}
sub-dist {Γ}{Δ}{Σ}{A}{B}{σ}{τ}{M} = extensionality λ x → lemma {x = x}
where
lemma : ∀ {x : Γ , A ∋ B} → ((M • σ) ⨟ τ) x ≡ ((subst τ M) • (σ ⨟ τ)) x
lemma {x = Z} = refl
lemma {x = S x} = refl

sub-app : ∀{Γ Δ} {σ : Subst Γ Δ} {L : Γ ⊢ ★}{M : Γ ⊢ ★}
→ ⟪ σ ⟫ (L · M)  ≡ (⟪ σ ⟫ L) · (⟪ σ ⟫ M)
sub-app = refl


## Interlude: congruences

In this section we establish congruence rules for the σ algebra operators • and ⨟ and for subst and its helper functions ext, rename, exts, and subst-zero. These congruence rules help with the equational reasoning in the later sections of this chapter.

[JGS: I would have liked to prove all of these via cong and cong₂, but I have not yet found a way to make that work. It seems that various implicit parameters get in the way.]

cong-ext : ∀{Γ Δ}{ρ ρ′ : Rename Γ Δ}{B}
→ (∀{A} → ρ ≡ ρ′ {A})
---------------------------------
→ ∀{A} → ext ρ {B = B} ≡ ext ρ′ {A}
cong-ext{Γ}{Δ}{ρ}{ρ′}{B} rr {A} = extensionality λ x → lemma {x}
where
lemma : ∀{x : Γ , B ∋ A} → ext ρ x ≡ ext ρ′ x
lemma {Z} = refl
lemma {S y} = cong S_ (cong-app rr y)

cong-rename : ∀{Γ Δ}{ρ ρ′ : Rename Γ Δ}{B}{M : Γ ⊢ B}
→ (∀{A} → ρ ≡ ρ′ {A})
------------------------
→ rename ρ M ≡ rename ρ′ M
cong-rename {M =  x} rr = cong _ (cong-app rr x)
cong-rename {ρ = ρ} {ρ′ = ρ′} {M = ƛ N} rr =
cong ƛ_ (cong-rename {ρ = ext ρ}{ρ′ = ext ρ′}{M = N} (cong-ext rr))
cong-rename {M = L · M} rr =
cong₂ _·_ (cong-rename rr) (cong-rename rr)

cong-exts : ∀{Γ Δ}{σ σ′ : Subst Γ Δ}{B}
→ (∀{A} → σ ≡ σ′ {A})
-----------------------------------
→ ∀{A} → exts σ {B = B} ≡ exts σ′ {A}
cong-exts{Γ}{Δ}{σ}{σ′}{B} ss {A} = extensionality λ x → lemma {x}
where
lemma : ∀{x} → exts σ x ≡ exts σ′ x
lemma {Z} = refl
lemma {S x} = cong (rename S_) (cong-app (ss {A}) x)

cong-sub : ∀{Γ Δ}{σ σ′ : Subst Γ Δ}{A}{M M′ : Γ ⊢ A}
→ (∀{A} → σ ≡ σ′ {A})  →  M ≡ M′
------------------------------
→ subst σ M ≡ subst σ′ M′
cong-sub {Γ} {Δ} {σ} {σ′} {A} { x} ss refl = cong-app ss x
cong-sub {Γ} {Δ} {σ} {σ′} {A} {ƛ M} ss refl =
cong ƛ_ (cong-sub {σ = exts σ}{σ′ = exts σ′} {M = M} (cong-exts ss) refl)
cong-sub {Γ} {Δ} {σ} {σ′} {A} {L · M} ss refl =
cong₂ _·_ (cong-sub {M = L} ss refl) (cong-sub {M = M} ss refl)

cong-sub-zero : ∀{Γ}{B : Type}{M M′ : Γ ⊢ B}
→ M ≡ M′
-----------------------------------------
→ ∀{A} → subst-zero M ≡ (subst-zero M′) {A}
cong-sub-zero {Γ}{B}{M}{M′} mm' {A} =
extensionality λ x → cong (λ z → subst-zero z x) mm'

cong-cons : ∀{Γ Δ}{A}{M N : Δ ⊢ A}{σ τ : Subst Γ Δ}
→ M ≡ N  →  (∀{A} → σ {A} ≡ τ {A})
--------------------------------
→ ∀{A} → (M • σ) {A} ≡ (N • τ) {A}
cong-cons{Γ}{Δ}{A}{M}{N}{σ}{τ} refl st {A′} = extensionality lemma
where
lemma : (x : Γ , A ∋ A′) → (M • σ) x ≡ (M • τ) x
lemma Z = refl
lemma (S x) = cong-app st x

cong-seq : ∀{Γ Δ Σ}{σ σ′ : Subst Γ Δ}{τ τ′ : Subst Δ Σ}
→ (∀{A} → σ {A} ≡ σ′ {A}) → (∀{A} → τ {A} ≡ τ′ {A})
→ ∀{A} → (σ ⨟ τ) {A} ≡ (σ′ ⨟ τ′) {A}
cong-seq {Γ}{Δ}{Σ}{σ}{σ′}{τ}{τ′} ss' tt' {A} = extensionality lemma
where
lemma : (x : Γ ∋ A) → (σ ⨟ τ) x ≡ (σ′ ⨟ τ′) x
lemma x =
begin
(σ ⨟ τ) x
≡⟨⟩
subst τ (σ x)
≡⟨ cong (subst τ) (cong-app ss' x) ⟩
subst τ (σ′ x)
≡⟨ cong-sub{M = σ′ x} tt' refl ⟩
subst τ′ (σ′ x)
≡⟨⟩
(σ′ ⨟ τ′) x
∎


## Relating rename, exts, ext, and subst-zero to the σ algebra

In this section we establish equations that relate subst and its helper functions (rename, exts, ext, and subst-zero) to terms in the σ algebra.

The first equation we prove is

rename ρ M ≡ ⟪ ren ρ ⟫ M              (rename-subst-ren)


Because subst uses the exts function, we need the following lemma which says that exts and ext do the same thing except that ext works on renamings and exts works on substitutions.

ren-ext : ∀ {Γ Δ}{B C : Type} {ρ : Rename Γ Δ}
→ ren (ext ρ {B = B}) ≡ exts (ren ρ) {C}
ren-ext {Γ}{Δ}{B}{C}{ρ} = extensionality λ x → lemma {x = x}
where
lemma : ∀ {x : Γ , B ∋ C} → (ren (ext ρ)) x ≡ exts (ren ρ) x
lemma {x = Z} = refl
lemma {x = S x} = refl


With this lemma in hand, the proof is a straightforward induction on the term M.

rename-subst-ren : ∀ {Γ Δ}{A} {ρ : Rename Γ Δ}{M : Γ ⊢ A}
→ rename ρ M ≡ ⟪ ren ρ ⟫ M
rename-subst-ren {M =  x} = refl
rename-subst-ren {ρ = ρ}{M = ƛ N} =
begin
rename ρ (ƛ N)
≡⟨⟩
ƛ rename (ext ρ) N
≡⟨ cong ƛ_ (rename-subst-ren {ρ = ext ρ}{M = N}) ⟩
ƛ ⟪ ren (ext ρ) ⟫ N
≡⟨ cong ƛ_ (cong-sub {M = N} ren-ext refl) ⟩
ƛ ⟪ exts (ren ρ) ⟫  N
≡⟨⟩
⟪ ren ρ ⟫ (ƛ N)
∎
rename-subst-ren {M = L · M} = cong₂ _·_ rename-subst-ren rename-subst-ren


The substitution ren S_ is equivalent to ↑.

ren-shift : ∀{Γ}{A}{B}
→ ren S_ ≡ ↑ {A = B} {A}
ren-shift {Γ}{A}{B} = extensionality λ x → lemma {x = x}
where
lemma : ∀ {x : Γ ∋ A} → ren (S_{B = B}) x ≡ ↑ {A = B} x
lemma {x = Z} = refl
lemma {x = S x} = refl


The substitution rename S_ M is equivalent to shifting: ⟪ ↑ ⟫ M.

rename-shift : ∀{Γ} {A} {B} {M : Γ ⊢ A}
→ rename (S_{B = B}) M ≡ ⟪ ↑ ⟫ M
rename-shift{Γ}{A}{B}{M} =
begin
rename S_ M
≡⟨ rename-subst-ren ⟩
⟪ ren S_ ⟫ M
≡⟨ cong-sub{M = M} ren-shift refl ⟩
⟪ ↑ ⟫ M
∎


Next we prove the equation exts-cons-shift, which states that exts is equivalent to cons’ing Z onto the sequence formed by applying σ and then shifting. The proof is by case analysis on the variable x, using rename-subst-ren for when x = S y.

exts-cons-shift : ∀{Γ Δ} {A B} {σ : Subst Γ Δ}
→ exts σ {A} {B} ≡ ( Z • (σ ⨟ ↑))
exts-cons-shift = extensionality λ x → lemma{x = x}
where
lemma : ∀{Γ Δ} {A B} {σ : Subst Γ Δ} {x : Γ , B ∋ A}
→ exts σ x ≡ ( Z • (σ ⨟ ↑)) x
lemma {x = Z} = refl
lemma {x = S y} = rename-subst-ren


As a corollary, we have a similar correspondence for ren (ext ρ).

ext-cons-Z-shift : ∀{Γ Δ} {ρ : Rename Γ Δ}{A}{B}
→ ren (ext ρ {B = B}) ≡ ( Z • (ren ρ ⨟ ↑)) {A}
ext-cons-Z-shift {Γ}{Δ}{ρ}{A}{B} =
begin
ren (ext ρ)
≡⟨ ren-ext ⟩
exts (ren ρ)
≡⟨ exts-cons-shift{σ = ren ρ} ⟩
(( Z) • (ren ρ ⨟ ↑))
∎


Finally, the subst-zero M substitution is equivalent to cons’ing M onto the identity substitution.

subst-Z-cons-ids : ∀{Γ}{A B : Type}{M : Γ ⊢ B}
→ subst-zero M ≡ (M • ids) {A}
subst-Z-cons-ids = extensionality λ x → lemma {x = x}
where
lemma : ∀{Γ}{A B : Type}{M : Γ ⊢ B}{x : Γ , B ∋ A}
→ subst-zero M x ≡ (M • ids) x
lemma {x = Z} = refl
lemma {x = S x} = refl


## Proofs of sub-abs, sub-id, and rename-id

The equation sub-abs follows immediately from the equation exts-cons-shift.

sub-abs : ∀{Γ Δ} {σ : Subst Γ Δ} {N : Γ , ★ ⊢ ★}
→ ⟪ σ ⟫ (ƛ N) ≡ ƛ ⟪ ( Z) • (σ ⨟ ↑) ⟫ N
sub-abs {σ = σ}{N = N} =
begin
⟪ σ ⟫ (ƛ N)
≡⟨⟩
ƛ ⟪ exts σ ⟫ N
≡⟨ cong ƛ_ (cong-sub{M = N} exts-cons-shift refl) ⟩
ƛ ⟪ ( Z) • (σ ⨟ ↑) ⟫ N
∎


The proof of sub-id requires the following lemma which says that extending the identity substitution produces the identity substitution.

exts-ids : ∀{Γ}{A B}
→ exts ids ≡ ids {Γ , B} {A}
exts-ids {Γ}{A}{B} = extensionality lemma
where lemma : (x : Γ , B ∋ A) → exts ids x ≡ ids x
lemma Z = refl
lemma (S x) = refl


The proof of ⟪ ids ⟫ M ≡ M now follows easily by induction on M, using exts-ids in the case for M ≡ ƛ N.

sub-id : ∀{Γ} {A} {M : Γ ⊢ A}
→ ⟪ ids ⟫ M ≡ M
sub-id {M =  x} = refl
sub-id {M = ƛ N} =
begin
⟪ ids ⟫ (ƛ N)
≡⟨⟩
ƛ ⟪ exts ids ⟫ N
≡⟨ cong ƛ_ (cong-sub{M = N} exts-ids refl)  ⟩
ƛ ⟪ ids ⟫ N
≡⟨ cong ƛ_ sub-id ⟩
ƛ N
∎
sub-id {M = L · M} = cong₂ _·_ sub-id sub-id


The rename-id equation is a corollary is sub-id.

rename-id : ∀ {Γ}{A} {M : Γ ⊢ A}
→ rename (λ {A} x → x) M ≡ M
rename-id {M = M} =
begin
rename (λ {A} x → x) M
≡⟨ rename-subst-ren  ⟩
⟪ ren (λ {A} x → x) ⟫ M
≡⟨⟩
⟪ ids ⟫ M
≡⟨ sub-id  ⟩
M
∎


## Proof of sub-idR

The proof of sub-idR follows directly from sub-id.

sub-idR : ∀{Γ Δ} {σ : Subst Γ Δ} {A}
→ (σ ⨟ ids) ≡ σ {A}
sub-idR {Γ}{σ = σ}{A} =
begin
σ ⨟ ids
≡⟨⟩
⟪ ids ⟫ ∘ σ
≡⟨ extensionality (λ x → sub-id) ⟩
σ
∎


## Proof of sub-sub

The sub-sub equation states that sequenced substitutions σ ⨟ τ are equivalent to first applying σ then applying τ.

⟪ τ ⟫ ⟪ σ ⟫ M  ≡ ⟪ σ ⨟ τ ⟫ M


The proof requires several lemmas. First, we need to prove the specialization for renaming.

rename ρ (rename ρ′ M) ≡ rename (ρ ∘ ρ′) M


This in turn requires the following lemma about ext.

compose-ext : ∀{Γ Δ Σ}{ρ : Rename Δ Σ} {ρ′ : Rename Γ Δ} {A B}
→ ((ext ρ) ∘ (ext ρ′)) ≡ ext (ρ ∘ ρ′) {B} {A}
compose-ext = extensionality λ x → lemma {x = x}
where
lemma : ∀{Γ Δ Σ}{ρ : Rename Δ Σ} {ρ′ : Rename Γ Δ} {A B} {x : Γ , B ∋ A}
→ ((ext ρ) ∘ (ext ρ′)) x ≡ ext (ρ ∘ ρ′) x
lemma {x = Z} = refl
lemma {x = S x} = refl


To prove that composing renamings is equivalent to applying one after the other using rename, we proceed by induction on the term M, using the compose-ext lemma in the case for M ≡ ƛ N.

compose-rename : ∀{Γ Δ Σ}{A}{M : Γ ⊢ A}{ρ : Rename Δ Σ}{ρ′ : Rename Γ Δ}
→ rename ρ (rename ρ′ M) ≡ rename (ρ ∘ ρ′) M
compose-rename {M =  x} = refl
compose-rename {Γ}{Δ}{Σ}{A}{ƛ N}{ρ}{ρ′} = cong ƛ_ G
where
G : rename (ext ρ) (rename (ext ρ′) N) ≡ rename (ext (ρ ∘ ρ′)) N
G =
begin
rename (ext ρ) (rename (ext ρ′) N)
≡⟨ compose-rename{ρ = ext ρ}{ρ′ = ext ρ′} ⟩
rename ((ext ρ) ∘ (ext ρ′)) N
≡⟨ cong-rename compose-ext ⟩
rename (ext (ρ ∘ ρ′)) N
∎
compose-rename {M = L · M} = cong₂ _·_ compose-rename compose-rename


The next lemma states that if a renaming and substitution commute on variables, then they also commute on terms. We explain the proof in detail below.

commute-subst-rename : ∀{Γ Δ}{M : Γ ⊢ ★}{σ : Subst Γ Δ}
{ρ : ∀{Γ} → Rename Γ (Γ , ★)}
→ (∀{x : Γ ∋ ★} → exts σ {B = ★} (ρ x) ≡ rename ρ (σ x))
→ subst (exts σ {B = ★}) (rename ρ M) ≡ rename ρ (subst σ M)
commute-subst-rename {M =  x} r = r
commute-subst-rename{Γ}{Δ}{ƛ N}{σ}{ρ} r =
cong ƛ_ (commute-subst-rename{Γ , ★}{Δ , ★}{N}
{exts σ}{ρ = ρ′} (λ {x} → H {x}))
where
ρ′ : ∀ {Γ} → Rename Γ (Γ , ★)
ρ′ {∅} = λ ()
ρ′ {Γ , ★} = ext ρ

H : {x : Γ , ★ ∋ ★} → exts (exts σ) (ext ρ x) ≡ rename (ext ρ) (exts σ x)
H {Z} = refl
H {S y} =
begin
exts (exts σ) (ext ρ (S y))
≡⟨⟩
rename S_ (exts σ (ρ y))
≡⟨ cong (rename S_) r ⟩
rename S_ (rename ρ (σ y))
≡⟨ compose-rename ⟩
rename (S_ ∘ ρ) (σ y)
≡⟨ cong-rename refl ⟩
rename ((ext ρ) ∘ S_) (σ y)
≡⟨ sym compose-rename ⟩
rename (ext ρ) (rename S_ (σ y))
≡⟨⟩
rename (ext ρ) (exts σ (S y))
∎
commute-subst-rename {M = L · M}{ρ = ρ} r =
cong₂ _·_ (commute-subst-rename{M = L}{ρ = ρ} r)
(commute-subst-rename{M = M}{ρ = ρ} r)


The proof is by induction on the term M.

• If M is a variable, then we use the premise to conclude.

• If M ≡ ƛ N, we conclude using the induction hypothesis for N. However, to use the induction hypothesis, we must show that

  exts (exts σ) (ext ρ x) ≡ rename (ext ρ) (exts σ x)


We prove this equation by cases on x.

• If x = Z, the two sides are equal by definition.

• If x = S y, we obtain the goal by the following equational reasoning.

exts (exts σ) (ext ρ (S y))   ≡ rename S_ (exts σ (ρ y))   ≡ rename S_ (rename S_ (σ (ρ y)      (by the premise)   ≡ rename (ext ρ) (exts σ (S y))      (by compose-rename)   ≡ rename ((ext ρ) ∘ S_) (σ y)   ≡ rename (ext ρ) (rename S_ (σ y))   (by compose-rename)   ≡ rename (ext ρ) (exts σ (S y))

• If M is an application, we obtain the goal using the induction hypothesis for each subterm.

The last lemma needed to prove sub-sub states that the exts function distributes with sequencing. It is a corollary of commute-subst-rename as described below. (It would have been nicer to prove this directly by equational reasoning in the σ algebra, but that would require the sub-assoc equation, whose proof depends on sub-sub, which in turn depends on this lemma.)

exts-seq : ∀{Γ Δ Δ′} {σ₁ : Subst Γ Δ} {σ₂ : Subst Δ Δ′}
→ ∀ {A} → (exts σ₁ ⨟ exts σ₂) {A} ≡ exts (σ₁ ⨟ σ₂)
exts-seq = extensionality λ x → lemma {x = x}
where
lemma : ∀{Γ Δ Δ′}{A}{x : Γ , ★ ∋ A} {σ₁ : Subst Γ Δ}{σ₂ : Subst Δ Δ′}
→ (exts σ₁ ⨟ exts σ₂) x ≡ exts (σ₁ ⨟ σ₂) x
lemma {x = Z} = refl
lemma {A = ★}{x = S x}{σ₁}{σ₂} =
begin
(exts σ₁ ⨟ exts σ₂) (S x)
≡⟨⟩
⟪ exts σ₂ ⟫ (rename S_ (σ₁ x))
≡⟨ commute-subst-rename{M = σ₁ x}{σ = σ₂}{ρ = S_} refl ⟩
rename S_ (⟪ σ₂ ⟫ (σ₁ x))
≡⟨⟩
rename S_ ((σ₁ ⨟ σ₂) x)
∎


The proof proceed by cases on x.

• If x = Z, the two sides are equal by the definition of exts and sequencing.

• If x = S x, we unfold the first use of exts and sequencing, then apply the lemma commute-subst-rename. We conclude by the definition of sequencing.

Now we come to the proof of sub-sub, which we explain below.

sub-sub : ∀{Γ Δ Σ}{A}{M : Γ ⊢ A} {σ₁ : Subst Γ Δ}{σ₂ : Subst Δ Σ}
→ ⟪ σ₂ ⟫ (⟪ σ₁ ⟫ M) ≡ ⟪ σ₁ ⨟ σ₂ ⟫ M
sub-sub {M =  x} = refl
sub-sub {Γ}{Δ}{Σ}{A}{ƛ N}{σ₁}{σ₂} =
begin
⟪ σ₂ ⟫ (⟪ σ₁ ⟫ (ƛ N))
≡⟨⟩
ƛ ⟪ exts σ₂ ⟫ (⟪ exts σ₁ ⟫ N)
≡⟨ cong ƛ_ (sub-sub{M = N}{σ₁ = exts σ₁}{σ₂ = exts σ₂}) ⟩
ƛ ⟪ exts σ₁ ⨟ exts σ₂ ⟫ N
≡⟨ cong ƛ_ (cong-sub{M = N} (λ {A} → exts-seq) refl) ⟩
ƛ ⟪ exts ( σ₁ ⨟ σ₂) ⟫ N
∎
sub-sub {M = L · M} = cong₂ _·_ (sub-sub{M = L}) (sub-sub{M = M})


We proceed by induction on the term M.

• If M = x, then both sides are equal to σ₂ (σ₁ x).

• If M = ƛ N, we first use the induction hypothesis to show that

ƛ ⟪ exts σ₂ ⟫ (⟪ exts σ₁ ⟫ N) ≡ ƛ ⟪ exts σ₁ ⨟ exts σ₂ ⟫ N

and then use the lemma exts-seq to show

ƛ ⟪ exts σ₁ ⨟ exts σ₂ ⟫ N ≡ ƛ ⟪ exts ( σ₁ ⨟ σ₂) ⟫ N

• If M is an application, we use the induction hypothesis for both subterms.

The following corollary of sub-sub specializes the first substitution to a renaming.

rename-subst : ∀{Γ Δ Δ′}{M : Γ ⊢ ★}{ρ : Rename Γ Δ}{σ : Subst Δ Δ′}
→ ⟪ σ ⟫ (rename ρ M) ≡ ⟪ σ ∘ ρ ⟫ M
rename-subst {Γ}{Δ}{Δ′}{M}{ρ}{σ} =
begin
⟪ σ ⟫ (rename ρ M)
≡⟨ cong ⟪ σ ⟫ (rename-subst-ren{M = M}) ⟩
⟪ σ ⟫ (⟪ ren ρ ⟫ M)
≡⟨ sub-sub{M = M} ⟩
⟪ ren ρ ⨟ σ ⟫ M
≡⟨⟩
⟪ σ ∘ ρ ⟫ M
∎


## Proof of sub-assoc

The proof of sub-assoc follows directly from sub-sub and the definition of sequencing.

sub-assoc : ∀{Γ Δ Σ Ψ : Context} {σ : Subst Γ Δ} {τ : Subst Δ Σ}
{θ : Subst Σ Ψ}
→ ∀{A} → (σ ⨟ τ) ⨟ θ ≡ (σ ⨟ τ ⨟ θ) {A}
sub-assoc {Γ}{Δ}{Σ}{Ψ}{σ}{τ}{θ}{A} = extensionality λ x → lemma{x = x}
where
lemma : ∀ {x : Γ ∋ A} → ((σ ⨟ τ) ⨟ θ) x ≡ (σ ⨟ τ ⨟ θ) x
lemma {x} =
begin
((σ ⨟ τ) ⨟ θ) x
≡⟨⟩
⟪ θ ⟫ (⟪ τ ⟫ (σ x))
≡⟨ sub-sub{M = σ x} ⟩
⟪ τ ⨟ θ ⟫ (σ x)
≡⟨⟩
(σ ⨟ τ ⨟ θ) x
∎


## Proof of subst-zero-exts-cons

The last equation we needed to prove subst-zero-exts-cons was sub-assoc, so we can now go ahead with its proof. We simply apply the equations for exts and subst-zero and then apply the σ algebra equation to arrive at the normal form M • σ.

subst-zero-exts-cons : ∀{Γ Δ}{σ : Subst Γ Δ}{B}{M : Δ ⊢ B}{A}
→ exts σ ⨟ subst-zero M ≡ (M • σ) {A}
subst-zero-exts-cons {Γ}{Δ}{σ}{B}{M}{A} =
begin
exts σ ⨟ subst-zero M
≡⟨ cong-seq exts-cons-shift subst-Z-cons-ids ⟩
( Z • (σ ⨟ ↑)) ⨟ (M • ids)
≡⟨ sub-dist ⟩
(⟪ M • ids ⟫ ( Z)) • ((σ ⨟ ↑) ⨟ (M • ids))
≡⟨ cong-cons (sub-head{σ = ids}) refl ⟩
M • ((σ ⨟ ↑) ⨟ (M • ids))
≡⟨ cong-cons refl (sub-assoc{σ = σ}) ⟩
M • (σ ⨟ (↑ ⨟ (M • ids)))
≡⟨ cong-cons refl (cong-seq{σ = σ} refl (sub-tail{M = M}{σ = ids})) ⟩
M • (σ ⨟ ids)
≡⟨ cong-cons refl (sub-idR{σ = σ}) ⟩
M • σ
∎


## Proof of the substitution lemma

We first prove the generalized form of the substitution lemma, showing that a substitution σ commutes with the substitution of M into N.

⟪ exts σ ⟫ N [ ⟪ σ ⟫ M ] ≡ ⟪ σ ⟫ (N [ M ])


This proof is where the σ algebra pays off. The proof is by direct equational reasoning. Starting with the left-hand side, we apply σ algebra equations, oriented left-to-right, until we arrive at the normal form

⟪ ⟪ σ ⟫ M • σ ⟫ N


We then do the same with the right-hand side, arriving at the same normal form.

subst-commute : ∀{Γ Δ}{N : Γ , ★ ⊢ ★}{M : Γ ⊢ ★}{σ : Subst Γ Δ }
→ ⟪ exts σ ⟫ N [ ⟪ σ ⟫ M ] ≡ ⟪ σ ⟫ (N [ M ])
subst-commute {Γ}{Δ}{N}{M}{σ} =
begin
⟪ exts σ ⟫ N [ ⟪ σ ⟫ M ]
≡⟨⟩
⟪ subst-zero (⟪ σ ⟫ M) ⟫ (⟪ exts σ ⟫ N)
≡⟨ cong-sub {M = ⟪ exts σ ⟫ N} subst-Z-cons-ids refl ⟩
⟪ ⟪ σ ⟫ M • ids ⟫ (⟪ exts σ ⟫ N)
≡⟨ sub-sub {M = N} ⟩
⟪ (exts σ) ⨟ ((⟪ σ ⟫ M) • ids) ⟫ N
≡⟨ cong-sub {M = N} (cong-seq exts-cons-shift refl) refl ⟩
⟪ ( Z • (σ ⨟ ↑)) ⨟ (⟪ σ ⟫ M • ids) ⟫ N
≡⟨ cong-sub {M = N} (sub-dist {M =  Z}) refl ⟩
⟪ ⟪ ⟪ σ ⟫ M • ids ⟫ ( Z) • ((σ ⨟ ↑) ⨟ (⟪ σ ⟫ M • ids)) ⟫ N
≡⟨⟩
⟪ ⟪ σ ⟫ M • ((σ ⨟ ↑) ⨟ (⟪ σ ⟫ M • ids)) ⟫ N
≡⟨ cong-sub{M = N} (cong-cons refl (sub-assoc{σ = σ})) refl ⟩
⟪ ⟪ σ ⟫ M • (σ ⨟ ↑ ⨟ ⟪ σ ⟫ M • ids) ⟫ N
≡⟨ cong-sub{M = N} refl refl ⟩
⟪ ⟪ σ ⟫ M • (σ ⨟ ids) ⟫ N
≡⟨ cong-sub{M = N} (cong-cons refl (sub-idR{σ = σ})) refl ⟩
⟪ ⟪ σ ⟫ M • σ ⟫ N
≡⟨ cong-sub{M = N} (cong-cons refl (sub-idL{σ = σ})) refl ⟩
⟪ ⟪ σ ⟫ M • (ids ⨟ σ) ⟫ N
≡⟨ cong-sub{M = N} (sym sub-dist) refl ⟩
⟪ M • ids ⨟ σ ⟫ N
≡⟨ sym (sub-sub{M = N}) ⟩
⟪ σ ⟫ (⟪ M • ids ⟫ N)
≡⟨ cong ⟪ σ ⟫ (sym (cong-sub{M = N} subst-Z-cons-ids refl)) ⟩
⟪ σ ⟫ (N [ M ])
∎


A corollary of subst-commute is that rename also commutes with substitution. In the proof below, we first exchange rename ρ for the substitution ⟪ ren ρ ⟫, and apply subst-commute, and then convert back to rename ρ.

rename-subst-commute : ∀{Γ Δ}{N : Γ , ★ ⊢ ★}{M : Γ ⊢ ★}{ρ : Rename Γ Δ }
→ (rename (ext ρ) N) [ rename ρ M ] ≡ rename ρ (N [ M ])
rename-subst-commute {Γ}{Δ}{N}{M}{ρ} =
begin
(rename (ext ρ) N) [ rename ρ M ]
≡⟨ cong-sub (cong-sub-zero (rename-subst-ren{M = M}))
(rename-subst-ren{M = N}) ⟩
(⟪ ren (ext ρ) ⟫ N) [ ⟪ ren ρ ⟫ M ]
≡⟨ cong-sub refl (cong-sub{M = N} ren-ext refl) ⟩
(⟪ exts (ren ρ) ⟫ N) [ ⟪ ren ρ ⟫ M ]
≡⟨ subst-commute{N = N} ⟩
subst (ren ρ) (N [ M ])
≡⟨ sym (rename-subst-ren) ⟩
rename ρ (N [ M ])
∎


To present the substitution lemma, we introduce the following notation for substituting a term M for index 1 within term N.

_〔_〕 : ∀ {Γ A B C}
→ Γ , B , C ⊢ A
→ Γ ⊢ B
---------
→ Γ , C ⊢ A
_〔_〕 {Γ} {A} {B} {C} N M =
subst {Γ , B , C} {Γ , C} (exts (subst-zero M)) {A} N


The substitution lemma is stated as follows and proved as a corollary of the subst-commute lemma.

substitution : ∀{Γ}{M : Γ , ★ , ★ ⊢ ★}{N : Γ , ★ ⊢ ★}{L : Γ ⊢ ★}
→ (M [ N ]) [ L ] ≡ (M 〔 L 〕) [ (N [ L ]) ]
substitution{M = M}{N = N}{L = L} =
sym (subst-commute{N = M}{M = N}{σ = subst-zero L})


## Notes

Most of the properties and proofs in this file are based on the paper Autosubst: Reasoning with de Bruijn Terms and Parallel Substitution by Schafer, Tebbi, and Smolka (ITP 2015). That paper, in turn, is based on the paper of Abadi, Cardelli, Curien, and Levy (1991) that defines the σ algebra.

## Unicode

This chapter uses the following unicode:

⟪  U+27EA  MATHEMATICAL LEFT DOUBLE ANGLE BRACKET (\<<)
⟫  U+27EA  MATHEMATICAL RIGHT DOUBLE ANGLE BRACKET (\>>)
↑  U+2191  UPWARDS ARROW (\u)
•  U+2022  BULLET (\bub)
⨟  U+2A1F  Z NOTATION SCHEMA COMPOSITION (C-x 8 RET Z NOTATION SCHEMA COMPOSITION)
〔  U+3014  LEFT TORTOISE SHELL BRACKET ($$option 9 on page 2) 〕 U+3015 RIGHT TORTOISE SHELL BRACKET ($$ option 9 on page 2)
`